Coefficient Bounds of Kamali-Type Starlike Functions Related with a Limacon-Shaped Domain. (19th October 2021) - Murugusundaramoorthy, Gangadharan; Shakeel, Ayesha; Kutbi, Marwan Amin
Abstract : In this article, we familiarize a subclass of Kamali-type starlike functions connected with limacon domain of bean shape. We examine certain initial coefficient bounds and Fekete-Szegö inequalities for the functions in this class. Analogous results have been acquired for the functions f − 1 and ξ / f ξ and also found the upper bound for the second Hankel determinant a 2 a 4 − a 3 2 .